Bronchoscopy, Imaging, and Concurrent Diseases in Dogs with Bronchiectasis: (2003–2014). (19th December 2015) - Johnson, L.R.; Johnson, E.G.; Vernau, W.; Kass, P.H.; Byrne, B.A.
Abstract : Background: Bronchiectasis is a permanent and debilitating sequel to chronic or severe airway injury, however, diseases associated with this condition are poorly defined. Objective: To evaluate results of diagnostic tests used to document bronchiectasis and to characterize underlying or concurrent disease processes. Animals: Eighty‐six dogs that had bronchoscopy performed and a diagnosis of bronchiectasis. Methods: Retrospective case series. Radiographs, computed tomography, and bronchoscopic findings were evaluated for features of bronchiectasis. Clinical diagnoses of pneumonia (aspiration, interstitial, foreign body, other), eosinophilic bronchopneumopathy (EBP), and inflammatory airway disease (IAD) were made based on results of history, physical examination, and diagnostic testing, including bronchoalveolar lavage fluid analysis and microbiology. Results: Bronchiectasis was diagnosed in 14% of dogs (86/621) that had bronchoscopy performed. Dogs ranged in age from 0.5 to 14 years with duration of signs from 3 days to 10 years. Bronchiectasis was documented during bronchoscopy in 79/86 dogs (92%), thoracic radiology in 50/83 dogs (60%), and CT in 34/34 dogs (100%). Concurrent airway collapse was detected during bronchoscopy in 50/86 dogs (58%), and focal or multifocal mucus plugging of segmental or subsegmental bronchi was found in 41/86 dogs (48%). Final diagnoses included pneumonia (45/86 dogs, 52%), EBP (10/86 dogs, 12%) and IAD (31/86 dogs, 36%). Bacteria were isolated in 24/86 cases (28%), with Streptococcus spp, Pasteurella spp, enteric organisms, and Stenotrophomonas isolated most frequently. Conclusions and Clinical Importance: Bronchiectasis can be anticipated in dogs with infectious or inflammatory respiratory disease. Advanced imaging and bronchoscopy are useful in making the diagnosis and identifying concurrent respiratory disease.